The Economics of Drinking: Evidence from the UW-Eau Claire Campus. - Bowlsby, Drew; Fennig, Robyn (My University, 2009)
The aim of this project is to find evidence of causes and impact of underage drinking, by administering a questionnaire survey of lifestyle habits amongst students at UWEC. The research project explores the following questions: (1) Incidence and consumption levels of alcohol, (2) Price elasticity of demand for alcohol and its policy implication, (3) impact of campus atmosphere and parental background and (4) brand loyalty.
Color poster with text and graphs.
Keywords: Drinking of alcoholic beverages--Economic aspects; Drinking of alcoholic beverages--Wisconsin--Eau Claire; University of Wisconsin--Eau Claire--Students--Alcohol use; College students--Alcohol use--Economic aspects; University of Wisconsin--Eau Claire--Students--Conduct of life; College students--Conduct of life; Posters